Diagnostic imaging - Armstrong, Peter , 1940-; Rockall, Andrea G.; Wastie, Martin L. (Wiley-Blackwell, 2009)
Suitable for medical students, junior doctors, trainee radiologists, and practising clinicians, this title explain how to interpret images; provide guidelines for interpreting images; discuss common diseases and the signs that can be seen using each imaging modality; and illustrate clinical problems with normal and abnormal images.